EFFECT OF OXYTOCIN MASSAGE USING LAVENDER ESSENTIAL OIL ON PROLACTIN LEVEL AND BREAST MILK PRODUCTION IN PRIMIPAROUS MOTHERS AFTER CAESAREAN DELIVERY - Panglukies Ratna Agustie; Suharyo Hadisaputro; Runjati Runjati; Ariawan Soejoenoes; Imam Djamaludin Mashudi; Melyana Nurul Widyawati (Belitung Nursing Journal, 2017)
Background: Low milk production is one of the barriers to exclusive breastfeeding. Oxytocin massage is considered as an alternative treatment, which combined with lavender essential oil as an aromatherapy.Objective: This study aims to examine the effect of oxytocin massage using lavender essential oil on the increase of levels of prolactin and milk production in primiparous mothers after caesarean section.Methods: This was a quasi-experimental study with non-equivalent control group design conducted in October-December 2016 at the General Hospital of Dr.H. Soewondo Kendal, Indonesia. There were 32 recruited by consecutive sampling, divided to be intervention (16 participants) and control group (16 participants). Prolactin hormone levels were measured using Enzyme-linked immunosorbent assay (ELIZA), breast milk production was measured based on the indicators of milk volume, urination and defecation frequency and sleep duration of babies; and infant’s weight was also measured by digital scale. Data were analyzed using Mann Whitney and Wilcoxon test.Results: The mean difference of prolactin hormone level in control group was 17.82 ng / ml while mean of difference of hormone prolactin level in intervention group was 132.13 ng / ml. There were statistically significant differences between intervention and control group in prolactin levels (p-value 0.000), milk volume (p-value 0.000), infant weight (p-value 0.000), urination frequency (p-value 0.017), defecation frequency (p-value 0.002), and infant sleep duration (p-value 0.000).Conclusion: There was a significant effect of the oxytocin massage using lavender essential oil on the increase of breast milk production and prolactin levels. Therefore, oxytocin massage using lavender essential oil can be used as an alternative treatment for midwives and other health professionals in an effort to increase milk production in postpartum.